Lions and brown bears colonized North America in multiple synchronous waves of dispersal across the Bering Land Bridge - Alexander T. Salis; Sarah C. E. Bray; Michael S. Y. Lee; Holly Heiniger; Ross Barnett; James A. Burns; Vladimir Doronichev; Daryl Fedje; Liubov Golovanova; C. Richard Harington; Bryan Hockett; Pavel Kosintsev; et al. (Molecular Ecology, 2022)
The Bering Land Bridge connecting North America and Eurasia was periodically exposed and inundated by oscillating sea levels during the Pleistocene glacial cycles. This land connection allowed the intermittent dispersal of animals, including humans, between Western Beringia (far northeast Asia) and Eastern Beringia (northwest North America), changing the faunal community composition of both continents. The Pleistocene glacial cycles also had profound impacts on temperature, precipitation and vegetation, impacting faunal community structure and demography. While these palaeoenvironmental impacts have been studied in many large herbivores from Beringia (e.g., bison, mammoths, horses), the Pleistocene population dynamics of the diverse guild of carnivorans present in the region are less well understood, due to their lower abundances. In this study, we analyse mitochondrial genome data from ancient brown bears ( Ursus arctos ; n = 103) and lions ( Panthera spp.; n = 39), two megafaunal carnivorans that dispersed into North America during the Pleistocene. Our results reveal striking synchronicity in the population dynamics of Beringian lions and brown bears, with multiple waves of dispersal across the Bering Land Bridge coinciding with glacial periods of low sea levels, as well as synchronous local extinctions in Eastern Beringia during Marine Isotope Stage 3. The evolutionary histories of these two taxa underline the crucial biogeographical role of the Bering Land Bridge in the distribution, turnover and maintenance of megafaunal populations in North America.

Correction to: Revealing the underlying mechanisms mediated by endophytic actinobacteria to enhance the rhizobia—chickpea (Cicer arietinum L.) symbiosis - Ting Xu; Q. A. Tuan Vo; Steve J. Barnett; Ross A. Ballard; Yonghua Zhu; Christopher M. M. Franco (Plant and Soil, 2022)

Revealing the underlying mechanisms mediated by endophytic actinobacteria to enhance the rhizobia - chickpea (Cicer arietinum L.) symbiosis - Ting Xu; Q. A. Tuan Vo; Steve J. Barnett; Ross A. Ballard; Yonghua Zhu; Christopher M. M. Franco (Plant and Soil, 2022)
Purpose The effects of endophytic actinobacterial strains, Microbispora sp. CP56, Actinomadura sp. CP84B, Streptomyces spp. CP200B and CP21A, on the chickpea- Mesorhizobium symbiosis, were investigated in planta , with the aim of revealing the underlying mechanisms of action. Methods The actinobacterial endophytes were co-inoculated with Mesorhizobium ciceri onto chickpea seedlings to study the effect on plant growth parameters, nodulation development and grain yield. The role of actinobacterial exudates on rhizobial growth was investigated, as was the role of root exudates of actinobacteria-colonized plants on the expression of rhizobial nod factors and biofilm formation. Changes in expression of plant flavonoids and bacterial N-fixation genes resulting from actinobacterial co-inoculation were assessed using qPCR. Results Application of actinobacterial endophytes, together with M. ciceri , showed growth promotion of chickpea with an increase in root nodule number and weight. Enhanced nodulation was accompanied by increases in total plant nitrogen, larger total plant weight and a 2–3-fold increase in grain yield. Factors associated with this tripartite symbiosis are promotion of rhizobial growth, earlier nodule formation, increased secondary root formation, up-regulated expression of genes related to flavonoid synthesis and nif genes. In addition, exudates of chickpea roots colonised with actinobacteria increased nodulation-related biological processes - rhizobial chemotaxis, biofilm formation and nod gene expression. Conclusion These endophytic actinobacteria positively affect many aspects of the chickpea- Mesorhizobium symbiosis resulting in increases in grain yield. Similar improvements recorded in chickpea growing in potted field soils, shows the potential to enhance chickpea production in the field.